THE INDICES AND INDICATORS OF SUSTAINABLE DEVELOPMENT AS AN ELEMENT OF THE QUALITY OF LIFE OF THE POPULATION OF THE RUSSIAN FEDERATION - Mikhail M. Rozhkov (Статистика и экономика)
The article presents the theoretical andmethodological basis for the formation ofquality management systems of life, andtheir relationship with sustainable development, which are the basis of variousindicators, indices and indicators. Techniques for the calculation and measurement of the index of quality of life, aswell as various projects for the development of indicators and indices of sustainable development, with an example of onesuch project.